2016
DOI: 10.3847/0004-637x/819/2/160
|View full text |Cite
|
Sign up to set email alerts
|

G11.2−0.3: The Young Remnant of a Stripped-Envelope Supernova

Abstract: We present results of a 400-ks Chandra observation of the young shell supernova remnant (SNR) G11.2−0.3, containing a pulsar and pulsar-wind nebula (PWN). We measure a mean expansion rate for the shell since 2000 of 0.0277 ± 0.0018% yr −1 , implying an age between 1400 and 2400 yr, and making G11.2−0.3 one of the youngest core-collapse SNRs in the Galaxy. However, we find very high absorption (A V ∼ 16 m ± 2 m ), confirming near-IR determinations and ruling out a claimed association with the possible historica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
42
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 67 publications
(87 reference statements)
3
42
2
Order By: Relevance
“…G11.2−0.3-G11.2−0.3 was first detected at X-ray wavelengths with Einstein HRI (Downes 1984) and was subsequently observed with ROSAT (Reynolds et al 1994) and with Chandra (Kaspi et al 2001;Roberts et al 2003;Lopez et al 2011;Borkowski et al 2016). The PWN and 65-ms period pulsar associated with G11.2−0.3 were discovered using ASCA observations (Vasisht et al 1996;Torii et al 1997), and Kaspi et al (2001) showed that the pulsar is only 8 from the geometric center of the SNR.…”
Section: Properties Of the Snrsmentioning
confidence: 99%
See 1 more Smart Citation
“…G11.2−0.3-G11.2−0.3 was first detected at X-ray wavelengths with Einstein HRI (Downes 1984) and was subsequently observed with ROSAT (Reynolds et al 1994) and with Chandra (Kaspi et al 2001;Roberts et al 2003;Lopez et al 2011;Borkowski et al 2016). The PWN and 65-ms period pulsar associated with G11.2−0.3 were discovered using ASCA observations (Vasisht et al 1996;Torii et al 1997), and Kaspi et al (2001) showed that the pulsar is only 8 from the geometric center of the SNR.…”
Section: Properties Of the Snrsmentioning
confidence: 99%
“…The PWN and 65-ms period pulsar associated with G11.2−0.3 were discovered using ASCA observations (Vasisht et al 1996;Torii et al 1997), and Kaspi et al (2001) showed that the pulsar is only 8 from the geometric center of the SNR. Borkowski et al (2016) used multiple epochs of Chandra observations to measure a shell expansion rate that implied an age of 1400-2400 years, making G11.2−0.3 one of the youngest identified CC SNRs in the Milky Way. Lopez et al (2011) performed a spatially-resolved spectroscopic analysis of 23 regions using Chandra data and found that the spectra were bestfit by a single absorbed, NEI component with absorbing columns of N H ≈ (2.1 − 2.9) × 10 22 cm −2 , temperatures of kT ≈ 0.6 − 1.4 keV, and ionization timescales of n e t ≈ (0.9 − 10) × 10 11 s cm −3 .…”
Section: Properties Of the Snrsmentioning
confidence: 99%
“…The very good agreement found in expansion rates for the Epoch I -III and Epoch II -III image pairs suggests that the magnitude of this bias is much smaller than statistical errors. This source of systematic errors was examined by Borkowski et al (2016) in their studies of the significantly brighter SNR G11.2−0.3 that expands 20% faster than Kes 73. They found it less important than statistical errors, and this is also expected to hold for Kes 73.…”
mentioning
confidence: 99%
“…We then smoothed this data cube with the multiscale partitioning method of Krishnamurthy et al (2010). We set the penalty parameter that controls smoothing to 0.015, the value that we found optimal for G11.2−0.3 (Borkowski et al 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation